Предмет: Математика,
автор: dashadance2208
-3(2x+3y)+7(-2x+4y)= -(7a+b)-8a-3b)=
-2(3x-1)+3(5-7x)=
-4(a-1)-5(2+a)=
7(x-4)-3(5+3x)=
Ответы
Автор ответа:
1
-3(2x+3y)+7(-2x+4y)= -6x - 9y - 14x + 28y = -20x + 19y
-(7a+b)-(8a-3b)= -7a - b - 8a + 3b = -15a + 2b
-2(3x-1)+3(5-7x)= -6x + 2 + 15 - 21x = -27x + 17
-4(a-1)-5(2+a)= -4a + 4 - 10 - 5a = -9a - 6
7(x-4)-3(5+3x)= 7x - 28 - 15 - 9x = -2x - 43
dashadance2208:
и вот ещё
Автор ответа:
0
1. -6х-9у-14х+28у= 19у-20х
2. -6х+2+15-21х=17-27х
3. -4а+4-10-5а=-9а-6
4. 7х-28-15-9х=-2х-43
5. -7а-b+8a+3b=a+4b
2. -6х+2+15-21х=17-27х
3. -4а+4-10-5а=-9а-6
4. 7х-28-15-9х=-2х-43
5. -7а-b+8a+3b=a+4b
Похожие вопросы
Предмет: Литература,
автор: vlasenkolizacka
Предмет: Математика,
автор: DrakoMallfoy
Предмет: Английский язык,
автор: sheradanov82
Предмет: Биология,
автор: llukrifer
Предмет: Информатика,
автор: vikavikafomenk